Islam dan Problematika Masyarakat Islam Modern Perspektif Syakib Arsalan - Sulton, Achmad (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2024)
The rapid and easy access to news in modern societies around the world, particularly news that showcases the lifestyles of advanced nations, has led to a shift in the lifestyle of modern communities. Consequently, the issues faced by modern societies have become increasingly complex. The purpose of this research is to analyze the role of Syakib Arsalan’s thinking in addressing the challenges of modern society. The study employs qualitative research methodology through a literature review of primary sources, specifically Syakib Arsalan’s work titled “Limadza Ta’akhoro al-Muslimun Wa Limadza Taqoddama Ghoiruhu,” as well as relevant secondary sources. The research findings indicate that by applying Syakib Arsalan’s ideas, reviving the spirit of jihad—both in terms of material wealth and personal commitment—can lead to the realization of a modern Islamic community that consistently embodies the spirit of jihad.